2014
DOI: 10.1089/fpd.2013.1638
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex PCR Assay for Simultaneous Detection of Escherichia coli O157:H7, Bacillus cereus, Vibrio parahaemolyticus, Salmonella spp., Listeria monocytogenes, and Staphylococcus aureus in Korean Ready-to-Eat Food

Abstract: A multiplex polymerase chain reaction (PCR) assay was developed for simultaneous detection of Escherichia coli O157:H7, Bacillus cereus, Vibrio parahaemolyticus, Salmonella spp., Listeria monocytogenes, and Staphylococcus aureus in various Korean ready-to-eat foods. The six specific primer pairs for multiplex PCR were selected based on the O157 antigen (rfbE) gene of E. coli O157:H7, the DNA gyrase subunit B (gyrB) gene of B. cereus, the toxin regulatory protein (toxR) gene of V. parahaemolyticus, the invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 23 publications
0
57
0
Order By: Relevance
“…Such advanced infrastructures will gradually erode the application of conventional techniques (such as, culture‐based microbial isolations and thin‐layer chromatography for toxin detection). Rapid techniques involving immunoassays and nucleic acid‐based methods for foodborne pathogen detection (Lee et al., ) and liquid chromatography–mass spectrometric methods for microbial toxin analysis (Berthiller et al., ) should be adopted to enable accurate and high‐throughput analysis.…”
Section: Food Safety Solutions and Future Perspectivesmentioning
confidence: 99%
“…Such advanced infrastructures will gradually erode the application of conventional techniques (such as, culture‐based microbial isolations and thin‐layer chromatography for toxin detection). Rapid techniques involving immunoassays and nucleic acid‐based methods for foodborne pathogen detection (Lee et al., ) and liquid chromatography–mass spectrometric methods for microbial toxin analysis (Berthiller et al., ) should be adopted to enable accurate and high‐throughput analysis.…”
Section: Food Safety Solutions and Future Perspectivesmentioning
confidence: 99%
“…Molecular tools such as PCR, multiplex PCR and realtime PCR employing virulence-associated genes such as the mpl gene, prfA gene (Rossmanith et al 2006) and ssrA gene (O'grady et al 2008) have been found rapid, specific, reproducible and reliable (Portnoy et al 2002;Gianfranceschi et al 2013;Hage et al 2014;Khan et al 2014). Several multiplex PCR assays have been developed for simultaneous detection of various food-borne pathogens like Salmonella, Escherichia coli, Staphylococcus and also Listeria (Park et al 2006;Kawasaki et al 2009;Lee et al 2014). Multiplex real-time PCR assay based on molecular beacon chemistry was developed recently which could detect eight food-borne pathogens (Salmonella enterica subsp.…”
Section: Diagnosismentioning
confidence: 99%
“…Primer design is critical in the multiplex PCR assay for the simultaneous amplification of multi-target DNA sequences to ensure specificity and sensitivity and to avoid crossreactions (Lee et al 2014). As the number of primers increases, the interaction effects also increase and may result in the formation of amplification artifacts, such as primer-dimers, truncated DNA fragments, non-specific bands or an absence of bands (Shrestha et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although specific primers amplify target DNA sequences, they do so with the differential amplification rates (Kim et al 2009). Taking into account these factors, lengths of multiple sets and melting temperatures (Tm) of primers must be similar Lee et al 2014). To establish a multiplex PCR method for simultaneous detection of three events of GM rice, we designed event-specific primers targeting to three GM rice events, namely, TT51-1, KMD1 and KF6.…”
Section: Discussionmentioning
confidence: 99%